Pola terapi pengobatan glaukoma di RSUD Hasri Ainun Habibie Kabupaten Gorontalo - Dizky Ramadani Putri Papeo; Ahmad Rifly Suleman; Kadaria Toana; Chinta Suryaningrum; Intan Nusi; Erika Dami; Fhigra Marfiah (Journal of Pharmaceutical and Sciences, 2023)
Background: Glaucoma is an eye condition that damages the optic nerve, causing loss of vision and even blindness. Damage to the optic nerve is often associated with high intraocular pressure (IOP), but in some cases, glaucoma can occur with normal IOP levels. There are several types of glaucoma, one of which is primary angle closure glaucoma. Angle-closure glaucoma can cause sudden and severe symptoms such as eye pain, headache, nausea, and blurred vision. Objective: This study aims to determine the pattern of glaucoma treatment therapy in one of the hospitals in Gorontalo District. Methods: Using patient medical record data, the SOAP method, and several literature studies. Results: Obtained some medical record data. From medical records, it found that the most widely used drugs to reduce intraocular pressure were tim ophthal eye drops 0.25% and glauceta 250 mg oral drug. Timolol maleate is the most commonly used beta adreno-receptor blocker, especially in the treatment of glaucoma. Glauceta 250 is a drug that contains Acetazolamide indicated to reduce the fluid that accumulates in the eyeball and reduce eyeball tension. Conclusion: From the results of the study, it can conclude that the treatment pattern of most glaucoma patients used the 0.25% tim ophthal drug with the results of 5 times the ophthal 0.25% team administration and the administration of 3 eye drops, namely HPMC + dextran 70 + glycerin, Potassium iodide + sodium iodide dan HPMC + dextran.